2015
DOI: 10.1158/1078-0432.ccr-15-0600
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Ramucirumab for Gastric Cancer

Abstract: The FDA approved ramucirumab (CYRAMZA; Eli Lilly and Company) for previously treated patients with advanced or metastatic gastric or gastroesophageal junction adenocarcinoma initially as monotherapy (April 21, 2014) and subsequently as combination therapy with paclitaxel (November 5, 2014). In the monotherapy trial, 355 patients in the indicated population were randomly allocated (2:1) to receive ramucirumab or placebo, 8 mg/kg intravenously every 2 weeks. In the combination trial, 665 patients were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 6 publications
0
63
0
Order By: Relevance
“…In 2014 the FDA approved ramucirumab, monoclonal antibody targeting vascular endothelial growth factor receptor-2 (VEGFR2) for the treatment of gastric and gastroesophageal junction adenocarcinomas (29). The approval was based in part on the results of the RAINBOW trial, which demonstrated that the combination of ramucirumab with paclitaxel significantly increases overall survival, as compared with placebo plus paclitaxel as second line therapy (9.6 vs. 7.4 months, P=0.017) in patients with advanced gastric and GE junction adenocarcinomas (30).…”
Section: Vascular Endothelial Growth Factor Receptor Numbermentioning
confidence: 99%
“…In 2014 the FDA approved ramucirumab, monoclonal antibody targeting vascular endothelial growth factor receptor-2 (VEGFR2) for the treatment of gastric and gastroesophageal junction adenocarcinomas (29). The approval was based in part on the results of the RAINBOW trial, which demonstrated that the combination of ramucirumab with paclitaxel significantly increases overall survival, as compared with placebo plus paclitaxel as second line therapy (9.6 vs. 7.4 months, P=0.017) in patients with advanced gastric and GE junction adenocarcinomas (30).…”
Section: Vascular Endothelial Growth Factor Receptor Numbermentioning
confidence: 99%
“…Bevacizumab (Avastin), a humanized VEGF-A neutralizing antibody, represents the first generation agent of anti-tumor angiogenesis drug, and has been approved to treat several types of malignancies in combination with cytotoxic chemotherapy, including colon, lung, and renal cancers [16]. Later on, inspired by this idea more VEGF/VEGFR antagonists, including ramucirumab, aflibercept, were developed and have also achieved clinical success [17,18]. Interestingly, several small molecular inhibitors of VEGFR, such as sorafenib and sunitinib, are capable of targeting multi-kinases and therefore exerting additive anti-tumor efficacy [18].…”
Section: Figure1mentioning
confidence: 99%
“…Furthermore, the results of a phase III clinical trial of ramucirumab plus paclitaxel versus placebo plus paclitaxel in the secondline treatment of metastatic gastric adenocarcinoma (RAINBOW trial) revealed signiicantly longer PFS and OS for the ramucirumab group [121], also leading to approval by the FDA of ramucirumab in combination with paclitaxel as a second-line therapy. Therefore, ramucirumab is for the moment, the only antiangiogenic agent that has been approved for the treatment of gastric carcinoma [122].…”
Section: Anti-vegf Receptor Monoclonal Antibodiesmentioning
confidence: 99%
“…Furthermore, the results of a phase III clinical trial of ramucirumab plus paclitaxel versus placebo plus paclitaxel in the secondline treatment of metastatic gastric adenocarcinoma (RAINBOW trial) revealed signiicantly longer PFS and OS for the ramucirumab group [121], also leading to approval by the FDA of ramucirumab in combination with paclitaxel as a second-line therapy. Therefore, ramucirumab is for the moment, the only antiangiogenic agent that has been approved for the treatment of gastric carcinoma [122].Endostar is a novel recombinant human endostatin, which was investigated [123] combined with SOX (S-1/oxaliplatin) for the irst-line treatment of patients with advanced gastric cancer; the results showed signiicantly beter PFS for the group including Endostar. More studies for the eicacy of Endostatin in stomach cancer setings are needed.…”
mentioning
confidence: 99%